Penanaman Karakter Cinta Tanah Air melalui Lagu-Lagu Nasional pada Siswa SD Kelas 5 di SDN Kejapanan 1 Pasuruan - Rohman, Muhammad Ali; Linggowati, Tri (Indonesian Journal Publisher, 2024)
The research in this thesis aims to determine the application of character education in Kejapana 1 Cinta Elementary School through national songs of the country. Early age is a very critical age for character building. Instilling in the younger generation the importance of good citizenship, in other words showing a sense of pride and love for the country. Expressing love for the country through the national anthem is considered one of the right ways to increase the love for the country. The simple words to the anthem are easy for children to understand and allow students to learn the words to the national anthem. The focus of this research is how Kejapanan 1 Elementary School instills a sense of love for the motherland through the national anthem. Data collection techniques through observation, interviews and documentation. Data validation techniques use triangulation of sources and techniques. The results showed that SDN 1 Kejapanan practiced Indonesian language character education with a sense of love for the country through the national anthem. The case of singing and understanding the lyrics of the national anthem can make students carry out behaviors/actions that reflect love for the homeland in everyday life. The national anthem acts as a means of learning, increasing intellectual intelligence, motivating, entertaining and socializing. This is reflected in the integration of student character values ​​into learning inside and outside the classroom. By following this path, the student's character can be improved and shaped for the better.